Association of cluster determinant 36, scavenger receptor class B type 1, and major facilitator superfamily domain containing the 2a genetic polymorphism with serum lipid profile in aging population with type 2 diabetes mellitus - Wang, Xixiang; Ma, Xiaojun; Xu, Jingjing; Guo, Yujie; Zhou, Shaobo; Yu, Huiyan; Yuan, Linhong (Frontiers in Nutrition, 2022)
Background: Lipid metabolism disorder commonly happens in subjects with type 2 diabetes mellitus (T2DM) which may be linked to genetic variants of lipid metabolism-related gene. However, few studies had explored the relationship between lipid metabolism-related gene polymorphism and serum lipid profile in aging subjects with T2DM. The present study was designed to explore the impact of genetic polymorphism of fatty acid translocase cluster determinant 36 (CD36), scavenger receptor class B member 1 (SCARB1) and major facilitator superfamily domain containing the 2a (MFSD2A) on the relationship between circulating lipids in aging subjects with T2DM. Methods: 205 T2DM patients and 205 age and gender matched control subjects were recruited. Information on demographic characteristics was collected by using a self-administered questionnaire. Fasting venous blood samples were taken for lipid-related gene genotyping and serum lipid profile measurement Chi-square test was used to compare percentage differences and to calculate Hardy-Weinberg equilibrium. Logistic regression and multiple linear regression were used to explore the risk or correlation between variables, and general linear model was used to compare the means of serum lipids between the groups. Results: In T2DM group, CD36 rs1054516 and MFSD2A rs12072037 were correlated with serum TC level. In control group, CD36 rs1049673 was correlated with serum HDL-C level. Meanwhile, T2DM subjects with MFSD2A rs12083239 (CG), MFSD2A rs4233508 (TT) and MFSD2A rs12072037 (AA) had higher TG level than control subjects. T2DM subjects with CD36 rs1049673 (CG, GG), CD36 rs1054516 (CT), CD36 rs2151916 (TT, CT), SCARB1 rs5888 (GG), MFSD2A rs12083239 (GG, CG), MFSD2A rs4233508 (TT) and MFSD2A rs12072037 (CA, AA) had lower HDL-C level than control subjects. T2DM subjects with MFSD2A rs12072037 (AA) had lower LDL-C level than control subjects. In dominant model, major genotype (GG) of SCARB1 gene was associated with the risk of T2DM (OR = 0.636, P = 0.032). Conclusions: Genetic polymorphisms of CD36, SCARB1 and MFSD2A were associated with serum lipids in T2DM subjects. SCARB1 rs5888 major genotype (GG) was a protective factor for T2DM. Large scale cohort study is required to determine the relationship between lipid metabolism-related gene polymorphism, serum lipid profile and T2DM in aging subjects.